1992
DOI: 10.1128/iai.60.7.2641-2647.1992
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of the antiglucocorticoid RU 486 on glucocorticoid and cytokine responses to Escherichia coli endotoxin

Abstract: The endogenous adrenocortical response to sepsis is critical for host survival. The in vivo interactions among the endogenous glucocorticoid response, the induction of cytokines, and host survival during endotoxemia were explored in this study by use of the glucocorticoid receptor antagonist RU 486. Male Lewis rats underwent sterile insertion of a right jugular venous catheter. After a 72-h recovery period, animals received a 50% lethal dose of Escherichia coli endotoxin (2.5 mg/kg) via the catheter after pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…This effect has been generally assumed to be due to a reduction in the levels of corticosterone but our data indicate that adrenaline plays a more important regulatory role than corticosterone since TNFa production was enhanced by the fl-adrenoceptor antagonist, propranolol but not by the corticosterone antagonist, RU 486. This result is in agreement with previous studies which demonstrated that RU 486 does not enhance systemic TNFa production in response to LPS at doses which effectively block the action of glucocorticoids (Hawes et al, 1992;Perretti et al, 1993) but is surprising since it is well established that glucocorticoids can inhibit TNFa production in vitro and in vivo. The implication is that the tissues responsible for systemic production of TNFa are more sensitive to the inhibitory action of /3-adrenoceptor agonists than to that of glucocorticoids.…”
Section: Discussionsupporting
confidence: 93%
“…This effect has been generally assumed to be due to a reduction in the levels of corticosterone but our data indicate that adrenaline plays a more important regulatory role than corticosterone since TNFa production was enhanced by the fl-adrenoceptor antagonist, propranolol but not by the corticosterone antagonist, RU 486. This result is in agreement with previous studies which demonstrated that RU 486 does not enhance systemic TNFa production in response to LPS at doses which effectively block the action of glucocorticoids (Hawes et al, 1992;Perretti et al, 1993) but is surprising since it is well established that glucocorticoids can inhibit TNFa production in vitro and in vivo. The implication is that the tissues responsible for systemic production of TNFa are more sensitive to the inhibitory action of /3-adrenoceptor agonists than to that of glucocorticoids.…”
Section: Discussionsupporting
confidence: 93%
“…8 Consequently, adrenalectomy or treatment with the GR antagonist RU486 results in high mortality in various models of infection. 9,10 In contrast, elevated GR expression is associated with increased resistance to endotoxic shock. 11 GCs modulate the function of leucocytes at different levels including the control of gene expression, enzymatic activity and cellular migration.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous GCs are produced during the course of inflammatory responses, including endotoxin shock [3,5,6]. Inhibition of the biosynthesis or effects of endogenously produced GCs in mice increases LPS-induced TNF production and lethality [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%